Acute (-)-Epicatechin Consumption: Effects on Local Vasodilation Following Resistance Exercise and High-Intensity Exercise Performance - Neil A. Schwarz; Andrew P. Theodore; Brandon R. Funderburg; Andy Waldhelm; Sarah K. McKinley-Barnard; Geoffrey M. Hudson (MDPI AG, 2020)
(-)-Epicatechin is a polyphenol previously shown to enhance vascular health. The purposes of the current studies were to determine the effect of acute (-)-epicatechin supplementation on local vasodilation in conjunction with resistance exercise (study 1) and on high-intensity exercise performance (study 2). For study 1, 11 men participated in two resistance exercise sessions, where they performed three sets of barbell curls while consuming 200 mg of 98% pure (-)-epicatechin or placebo. Measurements of total serum nitrate/nitrite and brachial artery diameter were acquired at baseline (pre-supplement), 90 min after supplement consumption (post-supplement), immediately post-exercise (post-exercise), and 30 min post-exercise (30 min post-exercise). For serum nitric oxide metabolites, no significant interaction between supplement and time nor significant main effect of time was observed (p = 0.38 and p = 0.20; respectively). For brachial artery diameter, no significant interaction between supplement and time was observed (p = 0.24). A significant main effect of time was observed for brachial artery diameter (p < 0.01) with post-exercise brachial artery diameter significantly greater diameter than all other time points (all p < 0.01). For study 2, six women and five men completed the 15.5 CrossFit® Open Workout three times. A familiarization session was performed first where the workout was performed without the consumption of a supplement. In a randomized, balanced fashion, 100 mg of 98% pure (-)-epicatechin or cellulose (placebo) was consumed two times per day for two days before testing sessions two and three. On the day of testing sessions two and three, 60 to 90 min before completing the workout, 200 mg of the assigned supplement was ingested with water. No significant difference was observed for time to complete the workout between testing sessions (p = 0.49). In conclusion, under the conditions of the current studies, acute (-)-epicatechin supplementation did not augment vasodilation in combination with resistance exercise, nor did it increase exercise performance in humans.